Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Aktivitas Belajar Dan Kemampuan Berpikir Kritis Siswa - Syofia Engla Sadita; Melva Zainil; Yanti Fitria; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
This research is motivated by the low learning activity and critical thinking skills of students in science learning in elementary schools. Students tend to be passive and lack understanding of the material presented. One effort that can be made is to apply the Guided Inquiry learning model. This study aims to determine the effect of the guided inquiry learning model on students' learning activities and critical thinking skills in science learning. The research conducted was a quantitative study using a quasi-experimental design involving two groups, namely the control group using conventional methods and the experimental group using the guided inquiry learning model. Data were collected through pretest and posttest. The results showed that the experimental group that applied the guided inquiry learning model experienced a significant increase compared to the control group using conventional learning. After being treated using the inquiry learning model, learning activities increased by 30.87% and critical thinking skills increased by 73.52%. The t-test showed a significant difference (p = 0.000) both in learning activities and critical thinking skills. For the correlation test, it was obtained as much as 0.832 and the percentage of the influence of the learning activity variable and critical thinking ability was 69.20%. Then in the N-gain analysis, the learning activity of the experimental group had an N-gain of 0.76 in the high category while the control group data was obtained as much as 0.45 which was in the medium category. The N-Gain analysis of critical thinking ability for the experimental group was 0.76 in the high category, while for the control class it was 0.4988 in the medium category.